Thelonious Monks musikalske univers : “Jazz and freedom go hand in hand” - Mortensen, Tore (Danish Yearbook of Musicology, 1995)
Thelonious Monk’s musical Universe: “Jazz and Freedom go hand in hand” The jazz composer and pianist Thelonious Sphere Monk held a unique position among musicians of the bebop generation. This was primarily due to his personal piano style, which apparently had no foundation in jazz tradition, and which had only a few imitators among the folIowing generations of musicians. The article discusses how Monk’s early profession as a gospel pianist in the late 1930s strongly influenced his musical concept as a whole in later years. The folIowing aspects of Monk’s musical style are examined: – Monk’s piano sound as aresult of a highly personal piano technique. – The compositional principles of Monk and how each composition appears as a unique specimen; typical is the concentration on a few motives or ruling principles, the ’‘technique of interrupting the 4/4-feeling by short circuiting the beat and locking the themes by the use of irregular metrical devices. These metrical irregularities together with unaccustomed harmonic progressions made heavy demands on the musicians who played with Monk. – Monk’s arrangement/recomposing of melodies from the standard repertoire. – Monk’s comp and solo techniques are analyzed in Well, You Needn’t and Ba-lue Bolivar Balues-are from the LP Live at the It Club. In conclusion Monk style is generally characterized by his emphasis on aspects of sound and rhythm as a means of moving and lifting his audience. Even though Monk’s instrumental style did not have many imitators, his musical approach, as documented in the article, had a great impact after World War II on musicians such as Sonny Rollins, John Coltrane, Charles Mingus and Horace Silver.